Transcriptomic comparison of primary human lung cells with lung tissue samples and the human A549 lung cell line highlights cell type specific responses during infections with influenza A virus - Bertrams, Wilhelm; Hönzke, Katja; Obermayer, Benedikt; Tönnies, Mario; Bauer, Torsten T.; Schneider, Paul; Neudecker, Jens; Rückert, Jens C.; Stiewe, Thorsten; Nist, Andrea; Eggeling, Stephan; Suttorp, Norbert; et al. (Scientific reports, 2022)
Influenza A virus (IAV) causes pandemics and annual epidemics of severe respiratory infections. A better understanding of the molecular regulation in tissue and cells upon IAV infection is needed to thoroughly understand pathogenesis. We analyzed IAV replication and gene expression induced by IAV strain H3N2 Panama in isolated primary human alveolar epithelial type II cells (AECIIs), the permanent A549 adenocarcinoma cell line, alveolar macrophages (AMs) and explanted human lung tissue by bulk RNA sequencing. Primary AECII exhibit in comparison to AM a broad set of strongly induced genes related to RIG-I and interferon (IFN) signaling. The response of AECII was partly mirrored in A549 cells. In human lung tissue, we observed induction of genes unlike in isolated cells. Viral RNA was used to correlate host cell gene expression changes with viral burden. While relative induction of key genes was similar, gene abundance was highest in AECII cells and AM, while weaker in the human lung (due to less IAV replication) and A549 cells (pointing to their limited suitability as a model). Correlation of host gene induction with viral burden allows a better understanding of the cell-type specific induction of pathways and a possible role of cellular crosstalk requiring intact tissue.